2016
DOI: 10.1214/15-aihp676
|View full text |Cite
|
Sign up to set email alerts
|

Liouville heat kernel: Regularity and bounds

Abstract: We initiate in this paper the study of analytic properties of the Liouville heat kernel. In particular, we establish regularity estimates on the heat kernel and derive non trivial lower and upper bounds.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 38 publications
4
50
0
Order By: Relevance
“…We will not directly use the Liouville heat kernel, so we do not say anything further about it here and instead refer the interested reader to [GRV14,MRVZ16,AK16,DZZ18a] for additional background.…”
Section: Overviewmentioning
confidence: 99%
“…We will not directly use the Liouville heat kernel, so we do not say anything further about it here and instead refer the interested reader to [GRV14,MRVZ16,AK16,DZZ18a] for additional background.…”
Section: Overviewmentioning
confidence: 99%
“…In [13,11], some non-universality aspects (when considering underlying logcorrelated fields other than GFF) for LQG distances were demonstrated. In [26,12], a type of equivalence between the Liouville graph distance and the heat kernel for Liouville Brownian motion was proved. In [10], it was shown that there is a single number which determines the distance exponents for a few reasonable choices of distances associated with LQG, as well as the distance exponents for random planar maps.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Actually, one can even show that p γ t (x, y) is a continuous function of (t, x, y) (see [23,Section 3]). In what follows, we will also consider the standard heat kernel p t (x, y) of the planar Brownian motion B on R 2 .…”
Section: Liouville Measure and Lbmmentioning
confidence: 99%
“…This elementary Euclidean argument can be formulated in the LQG context. Consider the Liouville heat kernel p γ t (x, y) of the Brownian motion associated to the metric tensor (1.1), which has been constructed in [15] (see also [23] for further properties). A moment of thought shows that finding the quantum exponent Δ of the set A consists of finding the number Δ such that…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation